The teaching of Documentation in Comunication Sciences degrees: study of its evolution from the analysis of the study plans - Cuevas Cerveró, María Aurora; Parra Valero, Pablo (Revista General de Información y Documentación, 2022)
The goal of this paper is to know how the subjects related to Library Science and Documentation have evolved in the Communication degrees taught in the Faculty of Information Sciences of the Complutense University of Madrid from its origin in 1971 to the present. The analysis methodology is based on the four study plans (1975 Plan, 1995 Plan, 2003 Plan and the 2011 Degree Plan) established in the three degrees that have been offered: Journalism, Audiovisual Communication and Advertising and Public Relations. Among the results obtained, we highlight that as the different study plans evolve, a growing trend towards specialization is observed, which finds its peak with the suppression of bachelor's degrees and the adoption of the European Higher Education Area, which this has led to a substantial decrease in the contents of Documentation to the point that there is currently only one compulsory subject in the Degree in Journalism and two electives in the Degree in Audiovisual Communication and in the Degree in Advertising and Public Relations.
Keywords: Information Sciences; Communication, Journalism; Library Science and Documentation; study programme; Complutense University of Madrid